Understanding process, power, and meaning in adaptive governance: a critical institutional reading - Frances Cleaver; Luke Whaley (Ecology and Society, 2018)
Adaptive governance continues to attract considerable interest in academic and policy circles. This is with good reason, given its increasing relevance in a globalized and changing world. At the same time, adaptive governance is the subject of a growing body of critical literature concerned with the ways in which it theorizes the social world. In this paper, we respond to these critiques, which we see as broadly concerning the process, power, and meaning dimensions of environmental and natural resource governance. We argue that adaptive governance theory would benefit from engaging constructively with critical institutionalism, a school of thought that, like adaptive governance, has one foot in commons scholarship. Critical institutionalism conceives of institutional change as a process of bricolage, where those involved piece together new arrangements from the resources to hand. This approach highlights the interplay of structure and agency, and illuminates how new governance arrangements form and come to be seen as natural in dynamic relation to the wider social and cultural landscape. We consider how these arrangements tend to reflect dominant power relations, whilst the plural nature of social life also provides scope for adaptation and transformative change.